2016
DOI: 10.18632/oncotarget.8780
|View full text |Cite|
|
Sign up to set email alerts
|

Nebivolol, a β1-adrenergic blocker, protects from peritoneal membrane damage induced during peritoneal dialysis

Abstract: Peritoneal dialysis (PD) is a form of renal replacement treatment, which employs the peritoneal membrane (PM) to eliminate toxins that cannot be removed by the kidney. The procedure itself, however, contributes to the loss of the PM ultrafiltration capacity (UFC), leading consequently to the technique malfunction. β-blockers have been considered deleterious for PM due to their association with loss of UFC and induction of fibrosis. Herein we analyzed the effects of Nebivolol, a new generation of β1-blocker, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
(76 reference statements)
0
15
0
Order By: Relevance
“…Guba et al published that Rapamycin decreased the synthesis of VEGF by endothelial cells [111]. In vivo exposure to PDF in a mice model, significant reduction in VEGF in PD effluent and in the number of both peritoneal blood and lymph vessels was founded [41].…”
Section: Anti-angiogenic and Anti-lymphangiogenic Agentsmentioning
confidence: 99%
“…Guba et al published that Rapamycin decreased the synthesis of VEGF by endothelial cells [111]. In vivo exposure to PDF in a mice model, significant reduction in VEGF in PD effluent and in the number of both peritoneal blood and lymph vessels was founded [41].…”
Section: Anti-angiogenic and Anti-lymphangiogenic Agentsmentioning
confidence: 99%
“…Blocking β1-adrenergic receptor (β1-AR) expressed in peritoneal MCs is another therapeutic strategy to reduce angiogenesis induced during PD [129] since it has been observed that the block of this receptor is related with anti-angiogenic effects [152]. Indeed, the β1-AR antagonist Nebivolol has demonstrated to attenuate submesothelial vessel formation in a mice model of PD obtained by instillation of PDFs through a peritoneal catheter.…”
Section: Othersmentioning
confidence: 99%
“…Indeed, the β1-AR antagonist Nebivolol has demonstrated to attenuate submesothelial vessel formation in a mice model of PD obtained by instillation of PDFs through a peritoneal catheter. This effect may be associated with its direct interaction with the β1-AR, but it could also be due to the reduction of fibrosis and MMT [129].…”
Section: Othersmentioning
confidence: 99%
“…74 A study in mouse model has suggested the role of beta-blocker nebivolol in preventing peritoneal dialysis induced fibrogenic responses. 75 Other drugs and agents which have been found to have some benefit in animal studies include rosiglitazone, N-acetyl cysteine, colchicine, angiotensin inhibition, thalidomide as well as biocompatible PD solutions. 60 However, the translation of these experimental evidence into clinical practice is awaited.…”
Section: Future Targetsmentioning
confidence: 99%